The effects of computerized performance monitoring: An ethical perspective - Hawk, Stephen R. (Journal of business ethics, 1994)
Considerable controversy has surrounded the use of computerized performance monitoring (CPM) by employers. Critics of this technology contend that CPM usage raises serious ethical concerns. Beliefs that the use of computerized performance monitors results in unfair performance evaluation, stress and health problems underlie much of the current concern over this technology. A field study was undertaken to provide empirical evidence that could be used to guide the design and use of computerized performance monitors to minimize these problems. One hundred forty three members of the Communication Workers of America participated in a cross sectional field study. The study examined the relationship between various monitoring system characteristics and employees' health problems, stress and satisfaction with the performance evaluation process. The ethical implications of the results are discussed.